PERBANDINGAN EFEK KOMBINASI TRAMADOL 100 mg + KETOROLAC 30 mg (DRIP) DENGAN KETOROLAC 30 mg (BOLUS) TERHADAP MEAN ARTERIAL PRESSURE (MAP) PASIEN POST TUR PROSTAT DI RUMAH SAKIT BHAYANGKARA ANTON SOEDJARWO PONTIANAK KALIMANTAN BARAT - Iis Suherni; Martyarini Budi; Fetty Kumala Dewi (Jurnal Inovasi Penelitian, 2023)
Benign Prostate Hyperplasia (BPH) is a disease of enlargement or hypertrophy of the prostate. BPH often causes dysfunction in the lower urinary tract in men and is most commonly found in elderly men. Transurethral prostate resection (TURP) remains the standard treatment for patients with moderate or severe BPH who require active treatment or who fail or do not want medical therapy. Pharmacologically, pain can be treated with analgesics, although analgesics can relieve pain effectively. Analgesic that can be given can be in the form of giving ketorolac 30 mg with tramadol 100 mg in postoperative pain. This study aims to compare the effect of the combination of tramadol 100 mg + ketorolac 30 mg (drip) with ketorolac 30 mg (bolus) on blood pressure as seen from the blood pressure value, namely the Mean Arterial Pressure (MAP) of post prostate TUR patients at Bhayangkara Anton Soedjarwo Hospital. Pontianak West Kalimantan. The design used a Quasy experimental design with a post test only nonequivalent control group design for 38 post TURP patients at Bhayangkara Anton Soedjarwo Hospital, Pontianak. Statistical independent samples test showed that there was no significant difference between MAP after being given a combination of 100 mg tramadol + 30 mg ketorolac (drip) and 30 mg ketorolac (bolus) with sig value > 0.05. With the results of this study, patients received quality services by preventing complications of post-TURP postoperative pain on blood pressure, namely the administration of a combination analgesic tramadol 100 mg + ketorolac 30 mg (drip) or with ketorolac 30 mg (bolus) so as to lower blood pressure